The quiet spectacle - Lee, May Ee (2017)
Growing up, I was greatly reminded by others and keenly aware of my rather self-contained demeanor. Finding a word to describe such a characteristic that is seen limiting by social standards is difficult as some might confused it with shyness. Self-consciousness in modern society reveals another spectrum of self-awareness or self-reflectiveness of one’s appearances, actions and behavioral patterns in accordance to meeting one’s or societal expectations. When manifested unhealthily, it would limit one’s propensity to achieve greater things both privately and socially. Personally, it is a painful for me to be reminded by my family members to “chin up and look” into the eyes of others. My sincerity and seriousness in my interaction with others is greatly hampered by my incapability to maintain eye contact. In some situations, I would use my hands to cover my face as naturally as I could to distract others from the momentarily revelation of my self-consciousness. I was afraid to be seen and judged by others, yet craved so ironically to be noticed and appreciated by others. Thus, I am interested in creating a balance of concealment and revelation in the behaviors of overly self-conscious individuals. Research done by Fenigstein (1975) affirms the importance of addressing such emotions in my project through his creation of a Self-Conscious Scale. His model consists of labelling different modes of self-consciousness to different display of emotional aspects in the private and public spheres. I was able to empathize that one of his standards of measurement of feeling self-conscious in the way we look falls under the realm of ‘Public Self-Consciousness’ (PuSC), ‘Appearance Consciousness (AC) and ‘Social Anxiety’ (SA). His study is still very much relevant in today’s contemporary society. Thus, I would like to reinforce the idea that feeling selfconscious should be treated as a common humanistic emotion, just like happiness and anger, which can be seen throughout centuries to the 21st century. Also, to formulate this intangible emotion to a concrete visualization, I was very enamored with Lindsey Wendler’s jewellery piece of masking scars as her mother was self-conscious about her scars on her neck. Her take on this stylish concealment coupled with the need to further its purpose aesthetically, enabled her to use medical knowledge to use healing materials with new fabric technology to soothe scarred skin. I was able to appreciate the fact even a self-conscious individual with an ‘unsightly’ emotional setback could still enjoy the joy of being stylish just like anyone else and the possibility of getting out there and conquer the world in their quiet way. I would like to use the most basic form of human senses that could exacerbate the feelings of self-consciousness which is Sight. One of the self-conscious tendencies extends to the individual being afraid of maintaining eyecontact lest they would be judged by their appearance and being confronted by the gaze of the others. Just as much as the individual who wishes to keep their self-conscious thoughts to themselves, the release and direct revelation could be projected with the covert use of acupressure massage. This project would experiment with the seamless amalgamation of concealment and revelation through a biological remedy with a cosmetic solution. Adapting it into a combination of familiar objects of eyewear and jewellery, the self-conscious individual would have the courage to wear them as others would be able to form visual linkages of my product to existing objects and not view them as out-of-the-world but a fashion choice. Thus, this product(s) would not only provide the wearer solace in knowing and keeping their condition hidden in view from others but create a “face” of the issue such that others would be distracted by it and the product could be the point of dialogue between two parties, enabling the wearer to cope and interact at the same time.